Torque-onset determination: Unintended consequences of the threshold method. (December 2016) - Dotan, Raffy; Jenkins, Glenn; O'Brien, Thomas D.; Hansen, Steve; Falk, Bareket
Abstract: Background: Compared with visual torque-onset-detection (TOD), threshold-based TOD produces onset bias, which increases with lower torques or rates of torque development (RTD). Purpose: To compare the effects of differential TOD-bias on common contractile parameters in two torque-disparate groups. Methods: Fifteen boys and 12 men performed maximal, explosive, isometric knee-extensions. Torque and EMG were recorded for each contraction. Best contractions were selected by peak torque (MVC) and peak RTD. Visual-TOD-based torque-time traces, electromechanical delays (EMD), and times to peak RTD (tRTD) were compared with corresponding data derived from fixed 4-N m- and relative 5%MVC-thresholds. Results: The 5%MVC TOD-biases were similar for boys and men, but the corresponding 4-N m-based biases were markedly different (40.3 ± 14.1 vs . 18.4 ± 7.1 ms, respectively; p < 0.001). Boys–men EMD differences were most affected, increasing from 5.0 ms (visual) to 26.9 ms (4 N m; p < 0.01). Men's visually-based torque kinetics tended to be faster than the boys' (NS), but the 4-N m-based kinetics erroneously depicted the boys as being much faster to any given %MVC (p < 0.001). Conclusions: When comparing contractile properties of dissimilar groups, e.g ., children vs . adults, threshold-based TOD methods can misrepresent reality and lead to erroneous conclusions. Relative-thresholds ( e.g ., 5% MVC) still introduce error, but group-comparisons are not confounded.